Genome-wide association studies of photosynthetic and agronomic traits, inter-character correlation and stability performance in core collections of cowpea [vigna unguiculata (l.) Walp] - Sansa, O.O. (Federal University of Agriculture, Abeokuta, 2024)
Climate change is threatening food security due to erratic and extreme weather conditions and germplasm resources hold potential for identifying adaptable and high yielding genotypes. The aim of this study were to assess genetic variability, stability performance and identify candidate genes driving drought tolerant and photosynthetic efficiency in some core collections of cowpea. One hundred and twelve cowpea accessions arranged in 8 × 14 Alpha lattice design with three replications were evaluated under well-watered and water-stressed conditions at Ibadan and Ikenne (2020 and 2021) and Kano (2021 and 2022). Drought was imposed at reproductive stage and agronomic traits were collected on well-watered and water-stressed plots. Photosynthesis traits were observed before and during stress imposition using PhotosynQ multispeq device. Data collected were subjected to analysis of variance, broad sense heritability, phenotypic, genotypic, environmental correlations. Thirty accessions comprising the best 20 and poorest 10 were selected for stability studies to identify high yielding and stable accessions across test environments. A genome-wide association study (GWAS) was also conducted to identify single nucleotide polymorphic (SNP) markers associated with agronomic and photosynthetic traits measured under well-water and water-stress conditions. Genomic DNA were extracted from one hundred accessions at the Bioscience center of IITA and genotyped at Diversity Array Technology sequencing platform located in Australia. A total of 19,000 DArTseq SNP markers were generated, after filtering and SNP quality checks, 9,210 SNP markers were used for GWAS. The results revealed significant (P<0.01) mean squares for accession, environment, accession x environment interactions for agronomic and photosynthetic traits measured under well-watered and water-stressed conditions. Across research conditions, accession, accession x water regime, accession x location in most of the measured agronomic traits were significant. Heritability ranged from 53 - 86% under well-watered and 35 - 80 % under water-stressed conditions. Genotypic correlations coefficients for the measured traits were mostly higher than phenotypic and environmental correlation in all the locations of study. Stability analysis revealed TVu-74 as the highest yielding accession and TVu-9913, TVu-9801 and TVu-14152 as the stable accessions across the test environments. Photosynthetic traits which include Quantum yield of photosystem II (Phi2), Ratio of incoming light lost via non-regulated process (PhiNO) and Ratio of incoming light that goes towards non-photochemical quenching (PhiNPQ) were significantly correlated with grain yield and was consistent across the years of study. GWAS results revealed thirty-eight SNPs were associated with all the measured traits. TVu-74, TVu-9913 and TVu-9801 were identified as high yielding and stable which can be used as potential parents in developing stable and high yielding cowpea varieties. Twenty-one candidate genes uncovered within the GWAS hits have functions relating to plant development and stress tolerance mechanisms. This study showed existence of genetic variability among the accessions for drought tolerant and photosynthetic efficiency providing an opportunity to identify high yield and stable accessions. GWAS revealed significant SNPs and candidate genes which are valuable genomic resources for marker-assisted breeding. Furthermore, this study shows genebanks as useful repository for identifying high yielding and adaptable accessions.